Comparative Study Between Apicectomy and Conservative Endodontic Treatment in Molar Teeth with Periapical Pathology - Gabriela Gelețu; Anca Melian; Gabriel Melian; N. Cotsoglou; Loredana Golovcencu (Romanian Society of Oral Rehabilitation, 2012)
To choose between conventional and surgical treatment is sometimes a dilemma faced by many clinicians. Modern endodontic therapy can achieve success predictably. Molar surgery is not so simple and the alternative methods have to be well evaluated and recommended. The purpose of this work was to compare the clinical and radiographic outcomes of nonsurgical treatment with those of endodontic surgery to determine what modalities offer more favourable outcomes into molars in a period of 4 years follow up. The modern endodontic therapy using ultrasound irrigation showed that healing process occurred in 95% of the treated molars compared to apicectomy or traditional endodontic therapy where only 89% or 86% of the molars presented no sign of relapse after 4 years.